A STUDY OF LANGUAGE STYLES USED IN THE QUEEN MOVIE - Khoimah, Khusnul (Universitas Islam Lamongan, 2019)
This study is conducted to analyze language styles used in The Queen movie. Specifically, the study is focused on the analysis of the classification of language styles which concerns to Martin Joos theory (1962). What makes this study is crucial to be analyzed is because the language styles used by the speaker have a unique set of items related to formal community. Linguistically, the language styles used by the speakers do exist due to the different circumstances and level, but formality is involved. This study is categorized as descriptive qualitative study since it is analyzed the data in the form of words. The data are collected from the script of The Queen movie. The writer makes herself as the key instrument that wants to find the statements of the problems itself. However, out of the classification of language styles proposed by Joos, this movie shows empirical data which is only found four styles used by the Queen Elizabeth. They are consultative, casual, intimate and formal style. Consultative style occurs when the Queen Elizabeth has two-way participation with other characters or it happens in the form of dialogue, whether the conversation happens with family, stranger and also to her work colleagues. Then, the Queen Elizabeth uses casual style when she feels people who talk to her is a group of friend who has close relationship. Hence, sometimes she leaves out some weak words in the beginning of the sentences because she assumes that other characters understand what she means. However, she uses intimate style only to her royal family. Although she gives a tiny clue to her royal family, it has made her royal family understand what she means. Besides, formal style is used by the main character when she presents on television program indicated with one-way participation.Key words: Styles, Language Styles, The Queen Movie